(untitled) (Journal of the College of Basic Education, 2022)
Learning is a modification and change in behavior that includes improvement in performance. Cognitive psychologists have paid attention to many variables related to learners’ preferred methods of acquiring concepts, absorbing information and addressing educational and social problems, and variables related to individual differences and cognitive functions. Perhaps one of the most prominent methods that facilitate the learning process is what is called (learning styles), as researchers have sought, since the past decades, to develop different methods and methods of learning.